Negotiating the responsibilities of collaborative undergraduate fieldcourses. Issue 3 (16th April 2015) - Bhakta, Amita; Dickinson, Jen; Moore, Kate; Mutinda, David; Mylam, Anna; Upton, Caroline
<x xml:space="preserve">Abstract</x> Undergraduate fieldcourses to destinations in the global South have received much critical scholarly and pedagogic attention. This article reflects on a third‐year Geography fieldcourse to Kenya, which aimed to collaborate with local partners in providing an immersive and co‐constitutive learning environment that transcended the politics of knowledge production defining the global South as a distanciated object of study. We shape our reflections on this fieldcourse through a conceptualisation of responsibility as a relational, inter‐subjective achievement borne out of negotiation and encounter. Focusing in particular on the trade‐offs that are required when taking into account different staff, students and partner organisations' positionalities, expectations and experiences, we argue that scholarship concerning the responsibilities of geographers' engagements with the global South needs to account for the emotional, embodied and affective challenges inherent in practising collaborative academic endeavour.